Copper Tolerance Mechanism of the Novel Marine Multi-Stress Tolerant Yeast Meyerozyma guilliermondii GXDK6 as Revealed by Integrated Omics Analysis - Bu, Ru; Yan, Bing; Sun, Huijie; Zhou, Mengcheng; Bai, Huashan; Cai, Xinghua; Mo, Xueyan; Su, Guijiao; Jiang, Chengjian (Frontiers in Microbiology, 2021)
Various agricultural products used in food fermentation are polluted by heavy metals, especially copper, which seriously endangers human health. Methods to remove copper with microbial strategies have gained interests. A novel Meyerozyma guilliermondii GXDK6 could survive independently under high stress of copper (1400 ppm). The copper tolerance mechanism of GXDK6 was revealed by integrated omics in this work. Whole-genome analysis showed that nine genes (i.e., CCC2, CTR3, FRE2, GGT, GST, CAT, SOD2, PXMP4, and HSP82) were related to GXDK6 copper tolerance. Copper stress elevated glutathione metabolism-related gene expression, glutathione content, and glutathione sulfur transferase activity, suggesting enhanced copper conjugation and detoxification in cells. The inhibited copper uptake by Ctr3 and enhanced copper efflux by Ccc2 contributed to the decrease in intracellular copper concentration. The improved expression of antioxidant enzyme genes (PXMP4, SOD2, and CAT), accompanied by the enhanced activities of antioxidant enzymes (peroxidase, superoxide dismutase, and catalase), decreased copper-induced reactive oxygen species production, protein carbonylation, lipid peroxidation, and cell death. The metabolite D-mannose against harsh stress conditions was beneficial to improving copper tolerance. This study contributed to understanding the copper tolerance mechanism of M. guilliermondii and its application in removing copper during fermentation.